Dynamic regulation of AtDAO1 and GH3 modulates auxin homeostasis - Mellor, Nathan L.; Band, Leah. R.; Pěnčík, Aleš; Novak, Ondrej; Rashed, Afaf; Holman, Tara; Wilson, Michael H.; Voss, Ute; Bishopp, Antony; King, John R.; Ljung, Karin; Bennett, Malcolm J.; et al. (National Academy of Sciences, 2016)
The hormone auxin is a key regulator of plant growth and development, and great progress has been made understanding auxin transport and signaling. Here we show that auxin metabolism and homeostasis are also regulated in a complex manner. The principal auxin degradation pathways in Arabidopsis include oxidation by AtDAO1/2 and conjugation by GH3s. Metabolic profiling of dao1-1 root tissues revealed a 50% decrease in the oxidation product oxIAA, an increase in the conjugated forms IAA-Asp and IAA-Glu of 438-fold and 240-fold respectively, while auxin remains close to wild type. By fitting parameter values to a mathematical model of these metabolic pathways we show that, in addition to reduced oxidation, both auxin biosynthesis and conjugation are increased in dao1-1. We then quantified gene expression in plantae, and found that transcripts of AtDAO1 and GH3 genes are increased in response to auxin, over different time scales and concentration ranges. Including this regulation of AtDAO1 and GH3 in an extended model reveals that auxin oxidation is more important for auxin homoeostasis at lower hormone concentrations, while auxin conjugation is most significant at high auxin levels. Finally, embedding our homeostasis model in a multicellular simulation to assess the spatial effect of the dao1-1 mutant shows that auxin increases in outer root tissues, in agreement with the dao1-1 mutant root hair phenotype. We conclude that auxin homeostasis is dependent on AtDAO1, acting in concert with GH3, to maintain auxin at optimal levels for plant growth and development.